Distributed Predefined-Time Optimization for Second-Order Systems under Detail-Balanced Graphs - Pablo De Villeros; Juan Diego Sánchez-Torres; Aldo Jonathan Muñoz-Vázquez; Michael Defoort; Guillermo Fernández-Anaya; Alexander Loukianov (Machines, 2023)
This paper studies the problem of distributed predefined-time optimization for leaderless consensus of second-order multi-agent systems under a class of weighted digraphs. The proposed framework has two main steps. In the first step, the agents communicate to perform a consensus-based distributed predefined-time optimization and to generate a constant optimal output reference for each agent. In the second step, each agent tracks its corresponding optimal output reference, using a sliding-mode controller to reach the global optimum in a predefined time, even under matched disturbances. The proposed algorithm relies explicitly on user-defined constant parameters. Numerical simulations are performed to validate the efficacy of the algorithm.